Ausencia y potencia : insinuaciones de unas materialidades sensibles (2021)
The starting point of this research is the experiences of mourning of the researchers; mourning associated with the death of loved ones, where as a consequence, not only lives are transformed, but spaces and the arrangement of objects in them. Going through the space and make the objects present, little by little the interest was turning to what they harbor: voices, smells, textures, and others. What also led to the researchers to trace artistic and theoretical works, to initiate a process of experimentation with audiovisual recording and to recompose the concept of object insensitive materialities. Consistent with experimentation and epistemological foundation, the research gave a light on how the sensible materialities took so much strength in this process, that allowed to conclude among others that, with the "absence" of the body-flesh of the loved ones, their presence is enhanced in the materialities, making them, with their different modes of existence have a life of their own.